Uma proposta de protocolo de codificação de libras para sistemas de tv digital. - Lemos, Felipe Herminio (2012)
Nowadays, the digital television systems do not have specific standards for sign languages (SL). The solution used in TV is to transmit a window with a SL interpreter over the video program. This solution is ineffective in several aspects: it has high operational costs, is dependent of a interpreter, and distract nondeaf viewers. In addition, it does not respects the regional differences in SLs. To reduce these problems, the main objective of this work is to propose a protocol to encode and transmit Brazilian sign language (LIBRAS) windows into digital television systems. In this propose, the frames of LIBRAS windows are not transmitted. Instead, a set of codes is transmitted, where each code is related to a visual representation of a sign in LIBRAS stored in the TV receiver. Thus it is possible to respect the regional differences of SL and to reduce the used bandwidth. Additionally, some strategies to represent sound effects, voice intonation and emotion nuances are also being investigated.